The Influence of JKT48 as Brand Ambassador, Brand Image, and Brand Schematicity of Erigo Apparel on Purchase Behavior - Oktaviyani, Dina; Abas, Novel Idris (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The study examined how the habit of purchasing high-end customer erigo apparel was influenced by the jkt48 selection asa brand ambassador. Methodology: The research employed a quantitative approach, utilizing Smart PLS for data analysis. A survey was conducted among 275 millennial respondents to gather data on their purchasing behavior, perceptions of JKT48 and Erigo, and brand schematicity. Result: The findings revealed that both the brand ambassador JKT48 and brand image have a positive influence on purchasing behavior. However, brand schematicity was found to mitigate the impact of these factors. This indicates that while a strong brand ambassador and positive brand image can drive purchases, a highly established brand schematicity may reduce the effectiveness of these marketing strategies. Applications/Originality/Value: The insights gained from this study can be valuable for fashion brands in developing effective marketing strategies. By understanding the interplay between brand ambassadors, brand image, and brand schematicity, marketers can optimize their campaigns to target specific consumer segments and drive sales. Additionally, the research contributes to the existing literature on consumer behavior and brand management.